ANALYSING TARGET COMMUNICATIVE NEEDS FOR ENGLISH FOR FOOD AND BEVERAGE SERVICE COURSE - Mahardika, A.A. Ngr. Yudha Martin (Jurnal Bahasa Lingua Scientia, 2018)
Every ESP course should be based on an analysis of needs. The current study was aimed at analysing the target needs related to the English for F&B Service course. It was revealed that; (1) The language functions of waiters in F&B Service department were closely related to the service sequence applied in the restaurants. Mostly, the functions for all hotels were the same, in which the differences were based on the characteristics of the hotel and restaurant, types of service, as well as the circumstances; (2) The language expressions needed were basically based on the tasks and varied based on the characteristics of the hotel and restaurant, types of service, the situation and condition. Results of the study implied that there was something beyond language skills that needs to be comprehended in order to be able to perform the tasks atF&B Service, especially as waiters. Task Based Learning with role play activities is suggested to facilitate the needs of communicative tasks.